Multisegmented polymers via step-growth and RAFT miniemulsion polymerization. Issue 41 (30th September 2021) - Guimarães, Thiago R.; Delafresnaye, Laura; Zhou, Dewen; Barner-Kowollik, Christopher; Zetterlund, Per B.
Abstract : We report a method to efficiently prepare multisegmented polymers via a combination of step-growth (SG) and reversible addition-fragmentation chain transfer (RAFT) polymerization. Abstract : We report a method to efficiently prepare multisegmented polymers via a combination of step-growth (SG) and reversible addition-fragmentation chain transfer (RAFT) polymerization. Initially, a SG-macroRAFT agent featuring several trithiocarbonate moieties distributed along the chain is synthesized by a catalyst-free Diels–Alder (DA) SG polymerization at ambient temperature. The SG-macroRAFT agent is subsequently employed as a multi RAFT transfer agent in a miniemulsion polymerization, yielding multisegmented polymers (up to M n = 100 000 g mol −1 ) confined in spherical nanoparticles (approx. 100 nm). We establish critical parameters such as the influence of the SG-macroRAFT agent composition and the hydrophilic nature of the initiator on the formation of the multisegmented polymer. Herein, we employed styrene as a model monomer, yet this platform technology can be readily translated to other vinylic monomers.